(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The purpose of this article is to create an empirical model of the export operations effectiveness logistic provision of the grain producers in Ukraine on the basis of existing and suggested institutional elements. It was investigated that the process of the material, informational and financial flows management provides their spatio-temporal synchronization with the aim of maximizing the systemic effect. Based on the integration of the Unified Agro Logistics System (UALS) of the Association of Agrarian Carriers of Ukraine and the author’s conceptual model of the transformation mechanism of the logistics system in the Ukrainian AIC grain product sub-complex, it was suggested an empirical model for the effective development of domestic grain logistics, which will enable the coverage of the entire logistics chain in the sub-complex, as the UALS offers relate to the logistics of intra-state grain flows in the «field-elevator» system, and the model we suggested – «elevator – elevator» or «elevator – port» – across Ukraine. It is determined that in the suggested empirical model, the objective function of the system is realized under conditions that the expendable physical functions are replaced by cheaper information flows in relation to manipulations with the grain. It is proved that the information-related relationship between the Monitoring Center of the logistics system and the Agrarian Exchange will help the effective development integrated model of the AIC grain-product sub-complex to establish communication with the world grain-market and to provide the analytical research and market prognosis in the internal grain market. Improvement and launch of the Electronic Trading System on the Agrarian Exchange for the creation of the commodity derivatives fully-fledged market in Ukraine will enable national producers to manage their price risks more effectively and to perform more predictable production activities.